The Supernatural after the Neuro-Turn edited by Pieter F. Craffert, John R. Baker, Michael J. Winkelman - Mayer, Gerhard A. (Journal of Scientific Exploration, 2022)
In the book chapter "Neurocognitive processes and supernatural beliefs," Andrew Newberg and David Yaden describe a basic cognitive process they call the "binary process." According to their model, this should contribute to the development of supernatural beliefs in addition to other processes. They understand this to be a general structuring process that organizes objects and abstract ideas into into dyads; that is, into relations of two, e.g., good and bad, happy and sad, natural and supernatural, right and wrong. The latter dyad points precisely to a problem I have with large parts of the book. The texts of the authors involved—all of whom are men—are almost universally characterized by such a binary thought structure. One of the editors, Pieter Craffert, a neuroanthropologist who teaches in South Africa, puts it succinctly in Chapter, “The supernatural: A range of neurocultural phenomena,” when he writes: If transcendental theorists are correct, there is not only a whole range of entities and phenomena with powerful influences on the world that beg explanation, but the scientific enterprise as we know it needs radical transformation. If non-transcendental theorists are correct, their theories pose a challenge to nearly all religions as well as local and cultural explanations of the phenomena. (p. 24) All authors of the book represent non-transcendental positions and attribute the category of the supernatural to “this-worldly” causes. It is not clear to me whether Craffert is aware that he leaves the area of scientific argumentation with the statement quoted above. With this escalation, there is only an either-or: Either they or we are right. It does not seem to occur to the authors that many of the non-transcendental explanations for supernatural interpretations of events and the arising of corresponding beliefs may be plausible and, in many cases, sufficient, but still do not capture the full picture. At least a more modest and reflective attitude that allows for this possibility is not reflected in the texts—with few exceptions.